Robust spatial-polarization hyperentanglement distribution of two-photon systems against collective noise. (8th February 2017) - Gao, Cheng-Yan; Wang, Guan-Yu; Alzahrani, Faris; Hobiny, Aatef; Deng, Fu-Guo
Abstract: Hyperentanglement is a significant resource for high-capacity quantum communication. Here we present a robust spatial-polarization hyperentanglement distribution scheme for two-photon systems. The error on the polarization states of two-photon systems transmitted from two paths can be corrected resorting to the robust time-bin entanglement which suffers little from the channel noise. The spatial bit-flip error takes place with a very small probability and the spatial phase-flip error can be precluded by adjusting the path-length of spatial modes. Using this scheme, the two parties in quantum communication can share a maximally hyperentangled state of two-photon systems in a deterministic way, which will improve the efficiency of quantum communication largely.